1907 Mo. Laws 229, An Act to Amend Article 3, Chapter 15, Revised Statutes of Missouri, 1899, Relating to Offenses Against Public and Private Property by Adding Two New Sections, to Be Known as Sections 1890a and 1890b, § 1. - (:unkn) unknown (General Publisher, 1907)
A person who with the intent to commit some crime, breaks and enters any building in the night time, and, for the purpose of committing any crime, uses or attempts to use nitro-glycerine, dynamite, gunpowder, or any other high explosive is guilty of burglary with explosives. § 1890b. Every person who shall be convicted by burglary with explosives, shall be punishable by imprisonment in the penitentiary not less than ten, nor more than twenty-five years.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME